2012
DOI: 10.1016/j.bbalip.2012.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endothelial lipase on cellular lipid composition

Abstract: Using mass spectrometry (MS), we examined the impact of endothelial lipase (EL) overexpression on the cellular phospholipid (PL) and triglyceride (TG) content of human aortic endothelial cells (HAEC) and of mouse plasma and liver tissue. In HAEC incubated with the major EL substrate, HDL, adenovirus (Ad)-mediated EL overexpression resulted in the generation of various lysophosphatidylcholine (LPC) and lysophosphatidylethanolamine (LPE) species in cell culture supernatants. While the cellular phosphatidylethano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…Previous work has shown that LIPG exerts phospholipase A1 activity towards high‐density lipoprotein (HDL)‐derived phosphatidylcholine (PC), releasing lipid products that become incorporated into intracellular PC and triacylglyceride (TAG) pools . Therefore, we investigated whether this also applies to breast cancer cells.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Previous work has shown that LIPG exerts phospholipase A1 activity towards high‐density lipoprotein (HDL)‐derived phosphatidylcholine (PC), releasing lipid products that become incorporated into intracellular PC and triacylglyceride (TAG) pools . Therefore, we investigated whether this also applies to breast cancer cells.…”
Section: Resultsmentioning
confidence: 96%
“…Previous work has shown that LIPG exerts phospholipase A1 activity towards high-density lipoprotein (HDL)-derived phosphatidylcholine (PC), 19 releasing lipid products that become incorporated into intracellular PC and triacylglyceride (TAG) pools. 7 Therefore, we investigated whether this also applies to breast cancer cells. First, endogenous expression of LIPG mRNA was measured in breast cancer cell lines of different subtypes: MCF-7 and T47D (ER+/HER2-), BT474 (ER +/HER2+), MDA-MB231 and MDA-MB-468 (ER-/HER2-) and SKBR3 and HCC1954 (ER-/HER2+).…”
Section: Lipg Enables Cancer Cells To Use Circulating Lipoproteins Asmentioning
confidence: 99%
See 2 more Smart Citations
“…[31][32][33][34][35] In addition, the lipolytic products generated by EL in HDL were previously shown to exert both putatively pro-and antiatherogenic activities. [36][37][38][39] Indeed, Hara et al 37 reported that EL deletion resulted in increased HDL and anti-inflammatory function in the plasma compartment; Ahmed et al 39 showed that HDL lipolysis by EL mediates repression of vascular cell adhesion molecule 1 expression. In view of the many anti-inflammatory properties of HDL, 40 any increased transendothelial HDL transport and hence extravascular enrichment of HDL in inflammation may be a mechanism aimed at the resolution of tissue inflammation.…”
Section: Discussionmentioning
confidence: 99%